THE DETERRITORIALIZATION CULTURE OF ISLAMIC BOARDING SCHOOLS: A NETNOGRAPHY STUDY OF LIVE STREAMING USERS OF KULIAH IHYA' TEMATIK AND NGARIKSA ON FACEBOOK - Khotimah, Nurul; Abdul Basit; Tamam, Mukhammad Khoiru; Putra, Pandika Adi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2024)
The teaching tradition of Islamic boarding schools has encountered deterritorialization. Islamic boarding schools that used to be distinguished by traditionality have transformed the management, financial, and learning traditions following digital developments. This article aims to examine the substantial shift in Islamic boarding school intellectual traditions from traditional to digital, which will then be called 'online recitation’, through live Facebook streaming content of Kuliah Ihya' Tematik (Ihya' Thematic Lectures) and Ngariksa (Questioning). The data were collected through documentation, surveys, and in-depth interviews involving kyai, production teams, and online santri (student) of two Facebook accounts: Ulil Abshar Abdalla (Ihya' Thematic Lectures) and Oman Fathurahman (Ngariksa). Data was analyzed using netnography through investigation, interaction, immersion, integration, and incarnation stages. The results showed values, rituals, heroes, and symbols in the deterritorialization culture of Islamic boarding schools. Followers of the online recitation get a social experience (becoming more sensitive to social issues) and a ritual experience (calmness in living life) after participating in the Ngaji online through live streaming or recorded playback. Research contributes to the development of Islamic communication science, where Islamic boarding schools, as the oldest Islamic educational institutions in Indonesia, can communicate with the broader community about learning activities in Islamic boarding schools through social media, which is of great interest to the public.